Effectiveness of endoscopic third ventriculostomy versus ventriculoperitoneal shunt in pediatric tumor-related hydrocephalus: A systematic review - Kusumo, Catur; Parenrengi, Muhammad Arifin; Suryaningtyas, Wihasto; Utomo, Budi; Haq, Irwan Barlian Immadoel; Apriawan, Tedy (Edelweiss Applied Science and Technology, 2025)
Hydrocephalus is a common neurological complication in pediatric brain tumor patients, particularly the obstructive type, with an incidence exceeding 50%. Tumor location critically influences cerebrospinal fluid (CSF) flow obstruction, often necessitating surgical intervention. This study compares the efficacy and safety of endoscopic third ventriculostomy (ETV) and ventriculoperitoneal (VP) shunt in managing tumor-related hydrocephalus in children. A systematic review was conducted following PRISMA 2020 guidelines, with literature searches performed in PubMed, Google Scholar, The Cochrane Library, and DOAJ. Studies were selected based on predefined inclusion and exclusion criteria, and risk of bias was assessed using the Joanna Briggs Institute’s critical appraisal tools. Four studies met the inclusion criteria—three evaluating ETV and one focusing on VP shunt complications. ETV demonstrated favorable outcomes in obstructive hydrocephalus, with fewer complications compared to VP shunts, which were more frequently associated with mechanical failures, particularly infections. Based on the findings, ETV is the preferred treatment for obstructive hydrocephalus secondary to brain tumors due to its higher efficacy and lower complication rates, whereas VP shunting remains a viable option for communicating hydrocephalus. Treatment decisions should consider hydrocephalus type, tumor location, and patient-specific factors.